Early and Delayed Effect of Cavity Disinfection with Chlorhexidine and Ozone on the Shear Bond Strength of Dentin to Glass Hybrid Restoration: An In Vitro Study - Murtatha M AL-Anezi; Shahbaa M Abduljabar (Dental Hypotheses, 2023)
Introduction: We aimed to evaluate the early and delayed effects of chlorhexidine (CHX) and ozone disinfection on the shear bond strength (SBS) of dentin to glass hybrid restoration. Methods: The occlusal surfaces of 60 extracted premolars were trimmed to obtain a flat dentinal surface and randomly divided into three groups, including distilled water (control), 2% CHX, and ozonized water. Each group was further subjected to a shear bond strength test after 24 hours and 3 months. Results: The overall model test (P <  0.001), disinfectant and time (P <  0.001), and time (P = 0.017) showed statistically significant differences among study groups. Yet, the type of disinfectant revealed a non-significant difference (P = 0.238). Post hoc tests showed SBS significantly decreasing over time in the control group (P <  0.001) while the difference between 24 hours and 3 months for the CHX (P = 0.880) and ozone (P = 0.983) groups was not significant. Conclusion: Within the inherent limitations of in vitro studies, it can be concluded that cavity disinfection with CHX and ozone before glass hybrid restoration had a significant effect on the stability of SBS to dentin over 3 months. The type of disinfectant revealed non-significant difference.